2018
DOI: 10.1186/s13045-018-0669-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelets and platelet receptors in cancer metastasis

Abstract: The interaction of tumor cells with platelets is a prerequisite for successful hematogenous metastatic dissemination. Upon tumor cell arrival in the blood, tumor cells immediately activate platelets to form a permissive microenvironment. Platelets protect tumor cells from shear forces and assault of NK cells, recruit myeloid cells by secretion of chemokines, and mediate an arrest of the tumor cell platelet embolus at the vascular wall. Subsequently, platelet-derived growth factors confer a mesenchymal-like phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
403
1
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 450 publications
(427 citation statements)
references
References 196 publications
(184 reference statements)
6
403
1
17
Order By: Relevance
“…Previous studies had uncovered that markedly elevated D-dimer levels were common in death patients with COVID-19 [8,9]. Similar to their results, we presumed that severe patients with COVID-19 had increased coagulation and fibrinolysis activity, marked by elevated D-dimer concentrations [10,11]. Notably, one severe patients in our study was developed into critical disease 7 day after admission with a D-dimer level of 13.61 mg/L, which further validated our speculation.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies had uncovered that markedly elevated D-dimer levels were common in death patients with COVID-19 [8,9]. Similar to their results, we presumed that severe patients with COVID-19 had increased coagulation and fibrinolysis activity, marked by elevated D-dimer concentrations [10,11]. Notably, one severe patients in our study was developed into critical disease 7 day after admission with a D-dimer level of 13.61 mg/L, which further validated our speculation.…”
Section: Discussionsupporting
confidence: 90%
“…We found that WJT spheres have up-regulated a coagulation cascade to recruit platelets as a survival strategy. Therefore suitable antithrombotic and antiplatelet concepts may be a valuable addition to future individualized, targeted therapies (76). However, the details of the molecular mechanism in platelet activation require further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets are conducive to tumor growth, angiogenesis and metastasis by producing growth and angiogenic factors, such as vascular endothelial growth factor and basic fibroblast growth factor. 27 Additionally, platelets provide favorable conditions for cancer cells by aggregating around them, including immune surveillance escape, shear stress protection, prosurvival signals, adhesion to the endothelium and extravasation. 28 Interactively, cancer cells, through their oncogenic transformation, can release many platelet agonists, such as adenosine diphosphate, thrombin, thromboxane and microparticles, which participate in platelet activation and contribute to thrombocythemia in cancer patients.…”
Section: Discussionmentioning
confidence: 99%